Design and validation of a closed loop variable hydrostatic pressure cytochamber - Constantinides, Georgios; Athanasiou, Kyriacos A.; Lanctot, Dan R. (My University, 1993)
Mechanical forces significantly affect growth, repair, and maintenance of the musculoskeletal system. Hydrostatic pressure is a type of force that most cells experience in vivo. In order to elucidate the mechanism of hydrostatic pressure effects on tissue culture cells, we designed and fabricated an apparatus that allows accurate pressurization at constant temperature. This cytochamber system was validated in three separate studies, in which cultured osteoblast-like cells were subjected to pre-described continuous pressure profiles at 37°C. These validation studies indicate that; a) Pressurization at 4MPa for 20 minutes induces significant cytoskeletal changes, as evidenced by tubulin and actin depolymerization, and increased adhesion at cellular interfaces. b) This pressurization also affects localization and staining of heat-shock proteins. c) A window of hydrostatic pressure, between 1. 5 to 2.5 MPa and applied continuously for two hours, exists that induces increased DNA synthesis. d) Other magnitudes of hydrostatic pressure (0.1, 2.0, and 6.0MPa) applied for two hours may enhance mineralization, as evidenced by significant increases in alkaline phosphatase. This closed-loop cytochamber allows the study of cell metabolism in response to hydrostatic pressure and demonstrates that this type of mechanical loading plays an important role in cell mechanotransduction.
Keywords: Cell culture; Metabolism; Musculoskeletal system; Cytology